Hydrogen evolution reaction catalyst with high catalytic activity by interplay between organic molecules and transition metal dichalcogenide monolayers. (April 2022) - Adofo, Laud Anim; Kim, Hyung Jin; Agyapong-Fordjour, Frederick Osei-Tutu; Thanh Nguyen, Huong Thi; Jin, Jeong Won; Kim, Yong In; Kim, Seon Je; Kim, Jung Ho; Boandoh, Stephen; Choi, Soo Ho; Lee, Su Jin; Yun, Seok Joon; et al.
Abstract: Introducing sulfur vacancies (SV ) in monolayer molybdenum disulfide (MoS2 ) is a well-known approach to activate the inert basal planes for efficient hydrogen evolution reaction (HER). However, higher SV induction accelerates the disruption of the crystal structure. We report an efficient method for improving catalytic activity and durability via covalent melamine (MEL) functionalization at SV sites in the basal plane of transition metal dichalcogenide (TMD) monolayers. Functionalized 2H–MoS2 requires only an overpotential of 160 mV at 100 mAcm −2 in acidic medium with chronoamperometric durability of more than 14 h at 30 mAcm −2 . Our theoretical results reveal that chemical functionalization creates novel HER active sites, where catalytic activity of the MEL−MoS2 catalyst arises from the interplay of the ring N sites of the MEL and the S atoms on the 2H–MoS2 surface. These findings of chemically coupled organic molecule−TMD system will pave new avenues for development of superior HER catalysts. Graphical abstract: Image 1 Highlights: Chemical functionalization creates an unprecedented form of HER active sites. HER activity of melamine−MoS2 catalyst arises from the interplay of the N sites of the melamine and S atoms on the MoS2 . Melamine functionalization at sulfur vacancy sites in defective MoS2 enhances HER performance while maintaining 2H phase. The instability caused by the defect was eliminated by using the sulfur vacancies as binding sites for melamine molecules.